Comparison of single radial immunodiffusion and ELISA for the quantification of immunoglobulin G in bovine colostrum, milk and calf sera. Issue 1 (1st January 2018) - Dunn, Amanda; Duffy, Catherine; Gordon, Alan; Morrison, Steven; Argűello, Anastasio; Welsh, Michael; Earley, Bernadette
ABSTRACT: The overall objective was to compare immunoglobulin G (IgG) concentrations measured by single radial immunodiffusion (sRID) and ELISA-based methods in samples of bovine colostrum and transition milk from contrasting breed types (Limousin × Friesian ( n = 10) and Holstein ( n = 10)). Jugular blood samples were collected at 48 h post-birth from beef ( n = 10) and dairy ( n = 10) calves and sera harvested subsequent to colostrum consumption. Absolute colostrum IgG values determined by ELISA showed poor agreement with mean (SD) IgG values measured using sRID, fixed bias (sRID – ELISA) was 31.89 (±9.84) mg/mL; having wide limits of agreement (12.61–51.17) and a low concordance coefficient (0.26). The agreement between ELISA and sRID when measuring serum IgG was greater than that of colostrum, fixed bias (sRID – ELISA) was 12.36 (±6.60) mg/mL; having narrower limits of agreement (−0.58 to 25.30) and serum IgG concentrations had a greater concordance coefficient (0.44) between samples. Calf sera IgG measured using the indirect zinc sulphate turbidity test showed a strong correlation with the sRID and ELISA methods ( P < .001), R 2 = 0.78 and R 2 = 0.77 respectively. Overall, the ELISA and sRID methodologies had a strong positive association with almost a twofold (1.8) difference between values; therefore, they provide diverse absolute values of IgG concentration.